Basal serum luteinizing hormone value as the screening biomarker in female central precocious puberty - Heo, Seung (Ann Pediatr Endocrinol Metab, 2019)
PURPOSE: Precocious puberty refers to the development of secondary sex characteristics before ages 8 and 9 years in girls and boys, respectively. Central precocious puberty (CPP) is caused by premature activation of the hypothalamus-pituitary-gonadal (HPG) axis and causes thelarche in girls before the age of 8. A gonadotropin-releasing hormone (GnRH) stimulation test is the standard diagnostic modality for diagnosing CPP. However, the test cannot always be used for screening because it is expensive and time-consuming. This study aimed to find alternative reliable screening parameters to identify HPG axis activation in girls <8 years old (CPP) and for girls 8–9 years old (early puberty, EP). METHODS: From January 2013 to June 2015, medical records from 196 girls younger than 9 years old with onset of breast development were reviewed, including 126 girls who had a bone age (BA) 1 year above their chronological age. All patients underwent a GnRH stimulation test, and 117 underwent pelvic sonography. The girls were divided into 4 groups based on age and whether the GnRH stimulation test showed evidence of central puberty. Subanalyses were also conducted within each group based on peak luteinizing hormone (LH) level quartiles. RESULTS: Basal serum LH level was the most sensitive marker for screening CPP and EP. The cutoff values were 0.245 IU/L for CPP under 8 years old (P=0.049, area under the curve [AUC]=0.764, 88% sensitivity, 48% specificity) and 0.275 IU/L for EP between 8–9 years old (P=0.005, AUC=0.813, 79% sensitivity, 77% specificity). Peak LH level decreased as BMI z-score among subgroups increased when there was no difference in BA; however, higher BA eliminated this effect. CONCLUSIONS: Basal serum LH level is a useful screening parameter for diagnosing CPP and EP in girls. Peak LH levels were lower with increasing BMI z-score, although older BA eliminated this effect.